(untitled) (International Journal of Engineering and Computer Science, 2017)
Delay-tolerant networking (DTN) is an approach to computer network architecture that seeks to address the technical issues in heterogeneous networks which may lack continuous network connectivity. Traditional routing algorithms try to establish a complete route from source to destination and then forward actual data. Due to lack of end to end connectivity, this is not possible in DTN. Also, security guarantees are difficult to establish in a network without persistent connectivity. This paper gives a fast greedy algorithm that intelligently selects next carrier node(s), optimizing the chances of successful delivery